x(3x^2 - 5x + 8)

When you distribute a constant, you multiply it. Here, it's to each value within the parentheses. So:

x(3x^{2} - 5x +8) = 3x^{2}(x) - 5x(x) + 8(x)

When multiplying unknown variables (like 'x'), the product is that variable raised to the sum (addition) of their power.

For example: x^{3}(x^{2}) = x^{3+2} = x^{5} , or: y^{5}(y^{4}) = y^{5+4} = y^{9}

Also, a variable with 'no exponent' actually has an exponent of 1. So, x = x^{1}.

For example: x^{3}(x) = x^{3+1} = x^{4}

To finish your question,

3x^{2}(x) - 5x(x) + 8(x) = 3x^{2+1} - 5x^{1+1} + 8x = 3x^{3} - 5x^{2} + 8x

## Comments

so 3x2(x).5x(x)+8(x)=3x2-1.5x1-1+8x=3x3.5x2+8x oh wow not simple - -_ !!!!